Comparison of Effectiveness of the Mindfulness-Based Cognitive Therapy and the Metacognition Treatment on Anxiety, Depression and Stress Among Breast Cancer Patients - Haji Seyed Javadi, Tahereh; Tajikzadeh, Fakhri; Bayat, Hossein; Eshraghi, Nasim; Roshandel, Zahra; Rahmani, Soheila (International Clinical Neuroscience Journal, 2018)
Background: The present study aimed to compare the effectiveness the metacognition treatment (MCT) and mindfulness-based cognitive therapy (MBCT) on anxiety, depression, and stress in the females with breast cancer. Methods: The planning of this study is through a quasi-experimental method of pretest and posttest type with control group. The target society of the research included every cancer patient who admitted to Tehran hospitals for breast cancer. Through assigned randomly, 12 patients were selected for the MCT group and 12 patients for the MBCT group, and the other were assigned control group. The data collection tools included depression, anxiety and stress scale - 21 items (DASS-21) questionnaire. For statistical analysis, descriptive tests and repeated measures analysis of variance were performed. Results: Data analysis with repeated multivariate measurements illustrated that there is a significant difference in the rate of depression, anxiety and stress, in three groups. Conclusion: According to our results, MBCT was more effective compared to metacognitive therapy.